UDP Pervasive Protocol Implementation for Smart Home Environment on MyRIO using LabVIEW - Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan; Sabriansyah Rizqika Akbar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Smart Home concept is to connect several devices to perform control and the device to be controlled to help any human needs. So it should have one device being Host and several devices being Client. The environment in this case is a home that there is too much technology that planted technologies that has much influence at human activities is called pervasive computing. The device communication should be has a protocol, at the research used UDP protocol because it doesn't need to negotiate before performing communication like a TCP. With UDP behavior did not use to validate at every send or deliver data because at Smart Home environment doesn't need a large or big data being processed. LabView used at this research based on previous research, but MyRIO has used this research to perform Client and Host performed by PC. So it can measure how usable the design that created. This research proves that LabView and MyRIO successfully implemented with the design that created to perform Pervasive Computing for Smart Home environment. Functional testing scenario conducted by every condition that on system environment, based on design all testing scenario successfully and working as well as expected.